Ultrasonic pulse technique for evaluation of mechanical damage in processed coffee beans - Mariana de Oliveira e Silva; Francisco Carlos Gomes; Stella Dellyzete Veiga Franco da Rosa (Semina: Ciências Agrárias, 2017)
The knowledge of the physical characteristics of the coffee bean allows the transition from the conventional storage model in bags to the silo storage, and as an indirect measure of the improvement and conservation of the quality of the stored grain. The elastic modulus allows comparisons on the strength of material. The variations of this occur due to its chemical composition, microstructures and material defects, being able to be used as indicator of the physical integrity of the grain. The ultrasonic pulse technique is an alternative to obtain the elastic modulus in a simple and non-destructive way. In this context, it was proposed the development of a non-destructive methodology that will perform the quality evaluation by determining the elastic modulus of the coffee beans. For this purpose, a reference silo was constructed, reproducing the storage conditions, and the elastic modulus values were determined. The values obtained by the Stress Wave Timer apparatus are between 2.54 and 4.23 MPa, with a maximum load of 8.32 kN, and a calculated vertical pressure of 1,526 kPa. To evaluate the impact of the storage conditions and the loads applied during the non-destructive test, laboratory tests applied in seeds were performed, and the tetrazolium test was the only one able to differentiate the samples. It was concluded that Stress Wave Timer was able to determine the elastic modulus values for the coffee bean mass and could be used as an indicative of the quality.